Analisis Pengaruh Etos Kerja Islami, Disiplin Kerja, Dan Gaya Kepemimpinan Terhadap Kinerja Pegawai Pada Kantor Wilayah Kementerian Agama Provinsi Jawa Tengah - Nisak, Saimatun; Adityawarman, Adityawarman (Diponegoro Journal of Islamic Economics and Business, 2021)
This study aims to examine the effect of Islamic work ethic, work discipline, and leadership style on employee performance at the Regional Office of the Ministry of Religious Central Java Province. Population in this research is employees at the Regional Office of the Ministry of Religious Central Java Province. 72 respondents are sample that are taken by using purposive random sampling techniques. Data collection method in this study uses questionnaire and processed by SPSS Statictics 23. Data are analysed by multiple linear regression analysis, goodness of fit test, and coefficient of determination. Determination coefficient shows that employee performance at the Regional Office of the Ministry of Religious Central Java Province is 87,2% affected by Islamic work ethic, work discipline, and leadership style. The rest 12,8% is explained by other variables outside this study. Then, Islamic work ethic, work discipline, and leadership style have a positive and significant effect on employee performance at the Regional Office of the Ministry of Religious Central Java Province either simultaneously or partially. Furthermore, among these three variables, the most dominant effect is Islamic work ethic.